2000
DOI: 10.1007/bf03190076
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of clozapine by rat brain: the role of flavin-containing monooxygenase (FMO) and cytochrome P450 enzymes

Abstract: The atypical antipsychotic clozapine has been reported to be metabolised mainly to its N-oxide and N-demethylated products. Brain, the target organ of clozapine, is known to contain numerous drug-metabolising enzymes which could alter the local concentrations of the drug. The metabolism of clozapine was, therefore, studied in rat brain preparations. Clozapine N-oxide was the major metabolic pathway in rat brain. We characterised the N-oxygenation of clozapine by rat brain preparations. The Km and Vmax values w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 18 publications
0
11
1
Order By: Relevance
“…The final version may differ from this version. the oxygenation of CLZ (Fang et al, 1998;Fang, 2000;Tugnait et al, 1997;. In the present study, we revealed that, under physiological conditions, the production of CLZ metabolites, CLZ-N-oxide and norCLZ, was not different between partial and full activation of FMOs in the presence and absence of the coenzyme NADPH, respectively.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…The final version may differ from this version. the oxygenation of CLZ (Fang et al, 1998;Fang, 2000;Tugnait et al, 1997;. In the present study, we revealed that, under physiological conditions, the production of CLZ metabolites, CLZ-N-oxide and norCLZ, was not different between partial and full activation of FMOs in the presence and absence of the coenzyme NADPH, respectively.…”
Section: Discussioncontrasting
confidence: 41%
“…FMOs and CYPs share many similarities in tissue distribution, subcellular location and substrate specificity (Krueger et al, 2005). FMOs, in particular FMO3, may be also involved in the N-oxygenation of CLZ (Tugnait et al, 1997;Fang et al, 1998;Fang, 2000;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Metabolizing enzymes, such as monoamine oxidase, flavin-containing monooxygenase, cytochrome P450, and glucuronosyltransferases have been identified in brain endothelial cells and brain tissue (el-Bacha and Minn, 1999;Fang, 2000;Gervasini et al, 2004;Strazielle et al, 2004). Hence, the stability of a compound in brain tissue needs to be examined in early drug discovery.…”
Section: What Determines the Extent Of Brain Penetration?mentioning
confidence: 99%
“…Its structure and function and the implications of its polymorphisms have been widely studied [8,12,13]. This enzyme has a wide substrate specificity, including the dietary-derived tertiary amines trimethylamine, tyramine and nicotine; commonly used drugs including cimetidine, ranitidine, clozapine, methimazole, itopride, ketoconazole, tamoxifen and sulindac sulfide; and agrichemicals, such as organophosphates and carbamates [14][15][16][17][18][19][20][21][22].…”
mentioning
confidence: 99%